Long-Distance Cross-Border Relationships in the Time of Covid-19 Pandemic: State, Emotion, and the Construction of Co-presence - Pananakhonsab, Wilasinee (Journal of Multidisciplinary Academic Research and Development (JMARD), 2024)
This article reflects the experiences of Thai women in long-distance cross-border (LDCB) relationships during the Coronavirus disease 2019 (COVID-19) pandemic. Two objectives were to study the effects of pandemic travel restrictions on LDCB couples and maintaining LDCB relations during the pandemic. Data was gathered by in-depth interviews with ten Thai women. Purposive sampling was used to select Thai women in LDCB relationships who were unable to meet their partners for at least two years. Results illustrated that mobility politics clearly affected emotions and relationships of LDCB couples. At first, most LDCB couples accepted the legitimacy of state border pandemic controls. However, inertia over more than two years transformed acceptance of state legitimacy into ambivalence because of policy uncertainty on border control in the time of Covid-19. Emotional instability and a longing for physical co-presence during the pandemic motivated LDCB couples to examine migration for the future, indicating that the imagined co-presence became essential for maintaining LDCB relationships when physical co-presence was absent.